Legal review on Personal Data Protection Act 2010: comparison with United Kingdom and European Union directive / Fatin Zulaikha Abu Samah … [et al.] - Abu Samah, Fatin Zulaikha; Jusoh@Zakaria, Azmi Johariruddin; Abdul Halim Lim, Hanis Haifaa; Ismail, Nurfarah Fatin (Faculty of Law, 2013)
This research discusses and analysed generally the Personal Data Protection Act 2010 (PDPA). The Act itself and its enforcement are compared with the Data Protection Act 1998 in United Kingdom (UK) and European Union Directive. Parliament of Malaysia has passed the PDPA with the objective to protect the personal data of individuals with respect to commercial transactions and is applicable to all businesses in the private sector in commercial transactions. The Act is still new in Malaysia and thus this is a research study to further determine the sufficiency and adequacy of the Act itself in upholding the protection of personal information in our country by comparing with the same act in UK and European Union Directive. At the end of the research, we have included few recommendations to be used for future reference.